Transcriptome analysis of gene expression profiling of infected macrophages between Brucella suis 1330 and live attenuated vaccine strain S2 displays mechanistic implication for regulation of virulence. (June 2018) - Jiang, Hui; Dong, Hao; Peng, Xiaowei; Feng, Yu; Zhu, Liangquan; Niu, Kai; Peng, Yong; Fan, Hongjie; Ding, Jiabo
Abstract: Brucellosis is one of the most common zoonotic epidemics worldwide. Vaccination against brucellosis is an important control strategy to prevent the disease in many high-prevalence regions. At present, Brucella vaccine strain S2 is the most widely used vaccine in China. To uncover the mechanisms underlying virulence attenuation of S2, in this study we characterized the transcriptional profile of S2 and 1330 infected macrophages by transcriptome analysis. The results revealed that expressions of 440 genes were significantly different between macrophages infected by 1330 and S2. Data analysis showed that in the gene ontology term, the different expressed genes involved in innate immune response, phagoctyosis, recognition, and inflammatory response were significantly enriched. Pathway enrichment analysis indicated that the genes involved in transcriptional misregulation in cancer, staphylococcus aureus infection pathways and NF-kappa B signaling pathway were significantly affected. To reveal the molecular mechanisms related to different expression profiles of infected macrophages, the transcription levels of the different genes between the two bacterial genomes were detected. In total, the transcription of 29 different genes was significantly changed in either culture medium or infected microphages. The results of this study can be conducive to the promotion of better understanding of the related mechanisms underlying virulence attenuation of S2 and interactions between host cells and Brucella strains. Highlights: The transcriptional profile of S2 and 1330 infected macrophages was studied by RNA-seq. The transcription levels of different genes between the two bacterial genomes were detected. This study promoted a better understanding of related mechanisms underlie virulence attenuation of S2 vaccine strain.